PELATIHAN PRODUKSI KONTEN KOMUNIKASI KESEHATAN UNTUK MEDIA SOSIAL BAGI PEGAWAI PUSKESMAS SE KOTA SEMARANG - Swita Amallia Hapsari; Mutia Rahmi Pratiwi; Choirul Ulil Albab; Naiza Rosalia; Hanif Pandu Suhito; Diah Lestari R (Politeknik Negeri Sriwijaya, 2023)
Puskesmas as a Regional Technical Implementation Unit (UPTD) which is under Dinas Kesehatan Kota Semarang was responsible for assisting public health in their rural area. There were 37 puskesmas in Semarang that also liable to share the information about public health in digital media such as Instagram. In order to improve the performance in digital media, puskesmas need to acknowledge the social media maintenance skill. By collaborating between Dinas Kesehatan Kota Semarang and Dian Nuswantoro University Communication Studies Program in the field of community service was carried out with teme of producing health communication content in social media. In this activity, we have to materials presented: content production in social media and reportase. Training activity was held on June 25, 2023 and was attended by 37 participant, they were social media managers at Puskesmas in Semarang. The methods in this activity is carried out three steps: Pre Activity, Activity, and Evaluation. Evaluation results were obtained from prepost test and discussion with participants. In the pretest, we have concluded that participants had good skills in understanding the Instagram features but did not knowing management and production of digital content. Participants understanding of reporting needs to be improved because 60% was reporting practices well. The results of this training post test showed that more than 90% of participant felt their understanding had increased about optimizing instagram media for increased content production and competence in public speaking for reporting on the implementation of puskesmas activity.